The Dinaric Vlachs/Morlachs in the Eastern Adriatic from the Fourteenth to the Sixteenth Centuries: How Many Identities? - Roksandić, Drago (Array, 2009)
History of Vlachs/Morlachs in the region of the Dinaric Alps since the Late Middle Ages to the end of the Early Modern period constitutes probably one of the major controversial problematics in the “shared history” of South Slavs in the Dinaric Alps. It is all the same when it is about “shared history” of the Habsburg Monarchy, the Venetian Republic as well as of the Ottoman Empire in the same space of their multiple border encounters for a historically long period of time. In spite of the fact that Vlachs/Morlachs are always related to specific socioeconomic and sociocultural “codes” beyond any political borderline, the history itself of those communities is always directly linked to the history of particular political realities in that region. One has to make a distinction between medieval and early modern polities in order to find out in what way each of those communities in the each of those political realities defines its legal status in secular and confessional terms, occupies available lands and migrates at the same time, integrates into social hierarchy, participates in the production and distribution of goods, constitutes a military power of their lords, etc., etc. Namely, it is always about a comparative history of the Vlachs/Morlacs in the Dinaric Alps and history of intercultural phenomena. Vlachs/Morlacs are related to “global societies” of their own in different ways. The same Vlach/Morlach communities are also perceived in different ways in distinctive political realities, what makes the problem of their distinctive identities extremely complicated ones. In any case, a concept of “multiple identities”, when it is about those communities, is intellectually the most productive one.